Binary Pattern Generation of Poetic Order in Sanskrit Poetic Meters - Kumar, Meena; Warneka, C. S.; Saxena, Saurabh (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2015)
The Pattern generation and Analysis is the technique of recognizing an object say, a target in combat space. The combat space T consists of targets of three types i) Wanted Targets W ii) Rejected Targets R iii) Unknown Targets U So that T = W ? R ? U The description of object is called pattern.Charaterization of pattern class by common properties shared by all of its members is another basic concept used in design of an pattern recognisation system. Main objective of this approach is to determine common properties from finite set of samples patterns and to examine a new pattern for a suitable switch. In signal processing , the role of input is vital to recognize objects. The input to the digital computer refers to any data or instructions entered into the memory. Data is a set of meaningful perceptual observations about an entity expressed in numerical ,alphabetical, graphical or mixed form. While Instructions refer to a set of action commands issued to CPU to tell a computer how to perform the tasks necessary to process data into information. Digital computer can accept the input via written/typed form through keyboard or the spoken/audio form through microphone. A great deal of work has been done in evaluating speech as a means of computer input. The present paper suggests the rhythmic syllable arrangements in various poetic meters as a means of audio input, directly producing binary code. Such binary syllable arrangement has been envisaged by Pingalacharya [1] . His Chhandas Shastra or science of poetic meters in Sanskrit is a well known classical treatise on Prosody. It deals with the rhythmic syllable arrangements in various poetic meters. According to Chhandas Shastra [2] every pronounced letter is either “Laghu” or Short [0] and “Guru” or Long[1] and each poetic meter is based on their fixed sequence[3]. Hence desired binary input sequence could be produced merely by utterance of corresponding syllables. Case studies of over 15 sets of such voice samples by male/ female/child  candidates were conducted and the resulting binary sequences are presented with corresponding accuracies.